KEPUASAN KERJA KARYAWAN PADA CV. MITRA BOGA TAMA - Yusnia Nasution (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
Abstract The purpose of this research is how the picture of the level of employee job satisfaction CV. Mitra Boga Tama in general are viewed from the six aspects of job satisfaction: the nature of work, attitude and superior leadership, the relationship between co-workers, working conditions, salaries and benefits, and opportunities to develop a career. It also determines which aspects of job satisfaction has been providing job satisfaction and aspects which do not provide job satisfaction. This type of study is a descriptive quantitative questionnaires as primary data collection tool which is supported by interviews. The research was conducted on 26 respondents who are employees in the sample of the population CV. Mitra Boga Tama. Sample technique used is total sampling that is taking on the entire sample population, this is because the amount is less than 100 respondents. Prior to the analysis of data, it first tested the validity and reliability of research instruments with SPSS 17.0 for Windows. Validity testing is done using correlation Pearson Product Moment in SPSS program for windows version 17.00. As for the reliability of testing instruments in this study, reliability tests carried out using Cronbach Alpha Formula techniques and by using the SPSS program for windows 17.00. The results showed that of the six aspects of job satisfaction: the nature of work, attitude and superior leadership, the relationship between co-workers, working conditions, salaries and benefits, and opportunities to develop a career, describing all aspects of employee job satisfaction. Moreover, if viewed a picture of the six aspects of job satisfaction that no aspect has been providing job satisfaction, four aspects of assessing only the neutral and the judge is not satisfied aspect is the aspect of salary and career development. From the results of this study can be in the know that the need for companies / leaders to improve the system or human resources personnel and employees need to do an evaluation for the purpose of the enterprise can be met or improved than before. Key words: Job Satisfaction